Pediatric Providers' Knowledge, Attitudes, Practice, and Barriers to Firearms Safety Counseling. Issue 10 (October 2021) - Bhalakia, Avni M.; DeMello, Annalyn; Beckworth, Kristen; Johnson, Brittany; Naik-Mathuria, Bindi
Abstract : This study looked at outpatient pediatric providers' attitudes, practice, and barriers to firearms safety counseling in Greater Houston. Survey respondents believe that it is important to discuss safe firearms storage with families at well checks, but only a few do so in practice, citing various barriers. We discuss potential solutions to reported barriers to incorporate firearms safety counseling into pediatric well child checks. Abstract : Objectives: Firearms-related injuries and deaths are a leading cause of death in children and young adults ages 5 to 24 years. This study evaluated the counseling practices and barriers to providing safe firearms storage education by pediatricians and advance practice providers. Methods: An online survey was sent to 296 pediatric outpatient providers in Houston, Texas. Pediatric providers were asked about demographics, knowledge, attitudes, and current practices regarding firearms safety counseling. Descriptive and comparative analyses were performed. Results: Survey respondents (N = 76) were 86% women and 87% physicians. Most (86%) agree that they should discuss firearms safety with parents, whereas only 32% report routine counseling. The most frequent barrier to providing education was insufficient time (63%), followed by unfamiliarity with guns (26%). Conclusions: Pediatric providers are interested in firearms safety counseling, but few incorporate it into their practice. Addressing barriers of time and comfort level around firearms are potential first steps to curbing a leading cause of injury death among children. Further research is needed to develop counseling methods that are time efficient and culturally competent for the pediatric office.